2017
DOI: 10.1007/s10549-017-4470-7
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, physical activity, and breast cancer survival among older breast cancer survivors in the Cancer Prevention Study-II Nutrition Cohort

Abstract: Higher BMI, pre- or post-diagnosis, was associated with a higher risk of BCSM in older patients, independent of comorbidities and stage at diagnosis. Weight management should be discussed even with women aged 65 years or older to lower rates of BCSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 32 publications
5
67
0
1
Order By: Relevance
“…First, the results of this study showed that exercise significantly affected the obesity of the subject breast cancer patients. The results of this study were similar to those of the previous parallel cohort study [16] conducted in the U.S., which argued that physical activities and obesity significantly influence cancer development and death. Particularly, the results of this study showed that a subject who did strength exercise for more days per week had a lower chance of becoming obese.…”
Section: Discussionsupporting
confidence: 89%
“…First, the results of this study showed that exercise significantly affected the obesity of the subject breast cancer patients. The results of this study were similar to those of the previous parallel cohort study [16] conducted in the U.S., which argued that physical activities and obesity significantly influence cancer development and death. Particularly, the results of this study showed that a subject who did strength exercise for more days per week had a lower chance of becoming obese.…”
Section: Discussionsupporting
confidence: 89%
“…The discussion of vegetable consumption was particularly infrequent in our study. Following healthy diets with an emphasis on plant‐based food consumption could protect from secondary cancers and decrease cancer related mortality . It was recently found that consuming vegetables is especially important for diversifying gut microbiome, which in turn lowers chronic inflammation, pain, fatigue, improves immunity, decreases tumorigenesis, and potentiates immunotherapeutic effects in cancer treatment and prevention …”
Section: Discussionmentioning
confidence: 99%
“…Weight loss recommendations in older obese and overweight survivors could play a major role in decreasing cancer related mortality, secondary obesity-related cancers, cancer recurrence, and comorbidities. 8,19,20 More research should investigate the reasons why these discussions are so infrequent. Societal stigma and provider discomfort discussing the sensitive nature of this subject matter might be reasons for infrequent discussion that could potentially be addressed.…”
Section: P-value Column % (N) Row % (N)mentioning
confidence: 99%
“…Studies of breast cancer mortality and survival rates have noted that adiposity is associated with reduced survival rates and higher rates of recurrence, irrespective of menopausal status and after adjustment for stage and treatment [68][69][70][71][72]. Additionally, obese patients with breast cancer often receive suboptimal treatment in terms of the doses of chemotherapy [73] and treatment appears to be less effective in patients with a BMI > 30 kg/m 2 [74].…”
Section: Breast Cancermentioning
confidence: 99%